The Effect of Foliar Spray by Mixture of Boron and Zinc on Yield and Fruit Quality of Var. AL Khelkhaly Olive Tree. (Journal of Hama University, 2020)
The aim of this research is to study the number and time of foliar spray by mixture of boron and zinc chelate with amino acids to the rate of the perfect, the stiminate, the vegetative, the fruit set, the yield and its quality to var (Al Khelkhaly). This research is implemented in cultivated field planted with olive trees in town (Qoumhana -Hama, province), on (2016, 2017) season. The application of foliar spray by mixture of boron and zinc chelate amino acids concentrate (350ppm B, 100ppm Zn) according to these application: 1- control without foliar spray; 2- one time before flowering; 3- two times before flowering and after fruit set; 4- three  times before flowering, after fruit set and during the pit hardening; 5- four times before flowering, after fruit set, during the pit hardening.The result demonstrates that there is no significant difference on the average of number of inflorescence on a branch and the complete number of flower on the branch. Whereas that mixture of  boron and zinc affect positively on the percentage of perfect flowers that the average of the first application reaches to (76.33 %), whereas in the control (65.94%), also on the fruit set. That the average of the fruit set reaches to (8.65 %) and in the control(4.98 %). These application of foliar spray by mixture of boron and zinc manifest the increase of tree production especially when we applied the application for two time that, average of the third application reaches (29.2 Kg / tree) where in the control (16.8 Kg / tree).